In vivo biodistribution and efficacy of peptide mediated delivery. - Järver, P; Mäger, I; Langel, Ü (2010)
To transverse the plasma membrane and gain access to the cellular interior is one of the major obstacles for many novel pharmaceutical molecules. Since the late 1990s, cell-penetrating peptides (CPPs) have been utilized as transport vectors for a broad spectrum of 'biological cargoes', ranging from inert gold particles to multifaceted macromolecules such as proteins and plasmids. Numerous studies have shown that CPPs are efficient carriers for bioactive cargoes in vitro. However, even though CPPs are versatile transport vectors, this does not guarantee they can be developed into useful pharmaceutical molecules. Nevertheless, recent progress in the field has shown CPPs to be effective for in vivo delivery with retained biological activity of a wide variety of bioactive cargoes into virtually any mammalian tissue. This review will focus on recent developments and applications for CPP delivery and distribution in vivo.